The Mediating Effect of Financial Self-Efficacy on the Financial Literacy-Behavior Relationship: A Case of Generation Y Professionals - Singh, Dipendra; Barreda, Albert A; Kageyama, Yoshimasa; Singh, Nripendra (The Economics and Finance Letters, 2019)
A comprehensive financial literacy questionnaire surveyed prospective psychological constructs as antecedents (financial literacy, economic perception, financial self-confidence, financial behavior, and personal financial performance) of applying financial self-efficacy in a large sample of working students in the hospitality and tourism industry. It is expected that financial literacy and economic perception are key antecedents of financial self-efficacy, which in turns may influence financial behaviors and personal financial performance in shaping a working student’s future skills for designing effective financial plans. For this purpose, the structural equations model was empirically tested. Moreover, the mediating indirect effects of financial self-efficacy in the relationships between financial literacy and economic environment on financial behavior and financial performance were tested through a two-phase methodological analysis. This study contributes to the literature by investigating the effects of financial self-efficacy, financial literacy and economic perception on personal financial behavior. The significance of the contribution is to propose and examine empirically a theory-based model of financial self-efficacy and financial behavior-performance in a service context among Generation Yers.